Decision making for determining promotional targets for the STMIK Kaputama campus using the Promethee method - Feni Yasari Br Surbakti; Achmad Fauzi; Suci Ramadani (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
Every foundation or educational institution certainly has efforts to maintain its existence amidst competition from educational institutions that continue to innovate to attract public interest in an educational institution . The results of good and appropriate promotion can be seen from the development of student admissions each year. To carry out promotions, of course you have to pay attention to things such as the type of school, travel time, number of computer science enthusiasts. Apart from that, determining promotional targets to get good, effective and efficient results. So a decision-making system is needed that is able to assist in the analysis of determining promotional targets at STMIK Kaputama. With the existence of a decision support system and based on STMIK Kaputama promotion target criteria, we are able to get the right promotion target results for the advancement of STMIK Kaputama development and realizing the vision and mission for the future, apart from that, so that prospective STMIK Kaputama students increase, because of the right promotion targets . To make decisions effective and efficient, this decision making system was built using the Promethee method , which is one of the decision making methods used to obtain a problem solution. Promethee is used to determine and produce decisions from several alternatives. From the results of the research conducted, it was found that the Promethee method was able to produce the best concise decisions.